PERAN KEPUASAN PELANGGAN DALAM MEMODERASI PENGARUH PERCEIVED VALUE TERHADAP LOYALITAS PELANGGAN - Budiyono Budiyono; Sutianingsih Sutianingsih (EKUITAS (Jurnal Ekonomi dan Keuangan), 2021)
The purpose of this study is to test and analyze how important the perceived value of Elsirestore's products is on customer loyalty, to test and analyze how much satisfaction increases with customer loyalty at Elsirestore, and to test and analyze perceived value of customer loyalty to Elsirestore's products with customer satisfaction. The method of data collection using a questionnaire conducted on respondents, namely consumers of Elsirestore. Data analysis techniques in testing the hypothesis of this study used multiple linear regression analysis techniques. The results show that the Perceived Value variable has a significant effect on Customer Loyalty, as evidenced by the p value = 0.037 (p <0.05), which means there is a significant effect, where the better the Perceived Value, the better the Customer Loyalty. Customer Satisfaction has a significant effect on Customer Loyalty as evidenced by the p value = 0.000 (p <0.05), which means that Customer Satisfaction has a significant effect on Customer Loyalty, where the better customer satisfaction, the better Customer Loyalty. Customer satisfaction moderates the effect of perceived value on customer loyalty at Elsirestore. This is indicated by the value of p value = <0.001 (p<0.05).